Identification of gastric cancer from speckle patterns - Andrade-Eraso, C. A. (2012)
Speckle technique is based on the light intensity distribution randomly formed when a laser light is reflected on a rough surface, creating a pattern of illuminated grains (constructively) and dark (destructive) on scales of 1 μm. When the samples are displaced or deformed, the speckle pattern is altered. In this paper we present speckle patterns obtained from samples of gastric mucosa that is physically altered for the carcinogenesis process. Biopsies were studied with different diagnoses and were grouped according to the characteristics of speckle patterns. Speckle patterns were obtained by illuminating the samples with green laser. Morphological parameters of the speckle patterns reveal existence of 3 descriptors: the average grain size, hydraulic radius and the radio of the Weddel disc, which showed a high, intermediate and low value. The comparison shows agreement between the histopathological diagnosis and the values obtained by the speckle technique, making this technique emerge as a new classification system for quantitative diagnosis of precancerous lesions.